Interstitial Lung Diseases using High Resolution Computed Tomography (HRCT) Images - B. SATYANARAYANA (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In the past decade years, medical image technologies have been rapidly growing. The x-rays, ultrasound (US), MRI scan and CT scan are the piliminary techniques to examine human diseases and CT techniques have more resolution images compared to other techniques. HRCT is another advanced technology derived from the CT family and working in 3D to capture the images. HRCT techniques are used to examine all humankind problems like heart, brain, breast, lung, kidney etc. The diagnosis accuracy depends on expert doctors, radiologists or pathologists and wrong judgment leads to wrong treatment or diagnosis. To overcome this, introduce computer-based technology instead of manual operation because of its more efficiency, accuracy and achieved by transfer learning methods, reviewed by the end of the chapter.